2003
DOI: 10.1108/01443330310790381
|View full text |Cite
|
Sign up to set email alerts
|

Jihad in monotheistic religions: implications for business and management

Abstract: The subject of Jihad has been a fiercly debated topic in the past few decades. Contradictory translations have been adopted by differing religious groups and political camps. In some quarters Jihad has been associated with violence and war. Other quarters perceive the Jihad to mean a striving within oneself and the struggle for self‐improvement. In this paper, the historical and contemporary perspectives of Christianity, Judaism, and Islam regarding Jihad are outlined. The evolution of the meaning of Jihad in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Cross-cultural studies to validate the MAWWWS in other Arab countries would provide useful comparisons within the Arab region and would fulfill the knowledge Attitudes towards working females gap on the differences and similarities between Arab countries, which too often have been treated as one entity. Ali et al (2003) have raised concerns for research collaboration between Arab countries as governments tend to place little value on research activities at universities. Omair (2008) however, found that increased number of researches on Arab women's advancement was published after year 2000, which does not only indicate that the topic of women's advancement is gaining more importance, but also perhaps the increased research activities in the Arab region.…”
Section: Future Researchmentioning
confidence: 99%
“…Cross-cultural studies to validate the MAWWWS in other Arab countries would provide useful comparisons within the Arab region and would fulfill the knowledge Attitudes towards working females gap on the differences and similarities between Arab countries, which too often have been treated as one entity. Ali et al (2003) have raised concerns for research collaboration between Arab countries as governments tend to place little value on research activities at universities. Omair (2008) however, found that increased number of researches on Arab women's advancement was published after year 2000, which does not only indicate that the topic of women's advancement is gaining more importance, but also perhaps the increased research activities in the Arab region.…”
Section: Future Researchmentioning
confidence: 99%
“…Similarly to the 'freedom fighters', interviewees are quite aware of their situation; are informed about their plight from a young age; and all desire change and have mobilized to achieve that aim. Our findings suggest that student involvement in social and political movements is motivated by the common interpretation of Islamic Jihad (holy struggle) as 'active participation in social improvement and economic development' (Ali et al, 2003).…”
Section: Development Of Knowledgeable and Reflexive Agents: Al-quds Umentioning
confidence: 96%
“…The term jihad, or struggle, is all too often equated with Islamic war or even terrorist activities because of a distorted interpretation of Islam by some politically motivated fringe groups, but its application to business life is much more positive. It should be interpreted as a striving with oneself, a struggle for selfimprovement by believers, so that they can carry out God's will more effectively (Ali, Gibbs, & Camp, 2003).…”
Section: Islamic Business Ethicsmentioning
confidence: 99%